Femtosecond Laser-Induced Electron Emission from Nanodiamond-Coated Tungsten Needle Tips - Tafel, Alexander; Meier, Stefan; Ristein, Jürgen; Hommelhoff, Peter (Physical Review Letters, 2019)
We present femtosecond laser-induced electron emission from nanodiamond-coated tungsten tips. Based on the shortness of the femtosecond laser pulses, electrons can be photoexcited for wavelengths from the infrared (1932 nm) to the ultraviolet (235 nm) because multiphoton excitation becomes efficient over the entire spectral range. Depending on the laser wavelength, we find different dominant emission channels identified by the number of photons needed to emit electrons. Based on the band alignment between tungsten and nanodiamond, the relevant emission channels can be identified as specific transitions in diamond and its graphitic boundaries. It is the combination of the character of initial and final states (i.e., bulk or surface-near, direct or indirect excitation in the diamond band structure), the number of photons providing the excitation energy, and the peak intensity of the laser pulses that determines the dominant excitation channel for photoemission. A specific feature of the hydrogen-terminated nanodiamond coating is its negative electron affinity that significantly lowers the work function and enables efficient emission from the conduction band minimum into vacuum without an energy barrier. Emission is stable for bunch charges of up to 400 electrons per laser pulse. We infer a normalized emittance of <0.20 nm rad and a normalized peak brightness of >1.2×1012 A m−2 sr−1. The properties of these tips are encouraging for their use as laser-triggered electron sources in applications such as ultrafast electron microscopy as well as diffraction and novel photonics-based laser accelerators.<br
Keywords: diamond-coated nanotip; ultrafast electron sources; emittance; brightness; electron microscopy